Unlocking Transparency for News Media Information Access: Mapping the ‘Information Curse’ in Tanzania’s extractive industry - Katunzi, Abdallah; Ndati , Ndeti; Thuo , Jane (University of Dar es Salaam Library Journal, 2025)
Tanzania is endowed with a wealth of extractive resources, including minerals and natural gas. However, alongside this potential arises the challenge of accessing vital information from Extractive Industries (EI). This article introduces the concept of the information curse, highlighting the detrimental effects of a lack of or limited transparency regarding access to critical Extractive Industry Information (EII) for news media. The inability of the news media to access vital non-exempt EII held by the government means the public relies on speculation, rumours, and pavement radio. The article contends that when news media access government-held EII and report on it, it cultivates a more informed society, encourages public discourse, enhances industry transparency, and significantly reduces the risk of unnecessary tensions and violence. The right-to-access information framework and the EITI Theory of Change inform the study presented in this paper. Data was collected through Key Informant Interviews (KII) and website content reviews to gather insights and thoughts about the topic. https://dx.doi.org/10.4314/udslj.v20i1.11